Potential asthma risk factors do not account for global asthma symptom prevalence patterns and time trends in children and adolescents - Rutter, Charlotte E.; Silverwood, Richard J.; Pearce, Neil; Strachan, David P. (The World Allergy Organization journal, 2024)
The International Study of Asthma and Allergies in Childhood (ISAAC) and the Global Asthma Network (GAN) conducted a series of global asthma prevalence surveys, between 1990 and 2020, in adolescents aged 13–14 and children aged 6–7 years. We used them to assess whether potential asthma risk factors explain global asthma symptom prevalence trends over this period. We fitted mixed-effects linear regression models to estimate associations between centre-level risk factor prevalence and both the mid-point asthma symptom prevalence and the change per decade. We also estimated the 2019 asthma symptom prevalence across all included centres. For adolescents, across 50 centres in 26 countries there was weak evidence that decreasing asthma prevalence over time was associated with regular fast-food consumption and frequent television viewing. However, frequent television viewing, along with heavy truck traffic, were associated with higher prevalence of asthma symptoms at the study mid-point. For children, across 41 centres in 21 countries, no risk factors were associated with time trends in asthma symptom prevalence, but truck traffic and paracetamol in the first year of life were associated with higher mid-point prevalence. We estimated the 2019 asthma symptom prevalence, across a total of 124 centres, to be 12.8% (11.4%, 14.2%) with little evidence of a difference by age. Low-income countries had lower prevalence (children 5.2% [2.5%, 7.8%], adolescents 5.3% [2.8%, 7.8%]), than lower-middle-, upper-middle- and high-income countries (all approximately 14–15%). Including risk factors in the models did not change the estimates. Potential asthma risk factors do not seem to explain the global prevalence patterns or time trends. Country income accounts for some of the differences, but the unexplained variation is very high.